Simulation and imaging of magnetic skyrmion in perpendicular magnetic anisotropy structures - Poh, Han Yin (2019)
Magnetic skyrmions are local whirls of the spin configuration in magnetic materials. Skyrmions are quasiparticles and they are by far the smallest magnetic (5 nm) structure which are stabilized by Dzyaloshinskii-Moriya interaction (DMI) in materials with perpendicular magnetic anisotropy. The low pinning current required and non-volatile nature of these magnetic skyrmions make it a promising candidate for memory devices. In addition, skyrmion has low energy consumptions and it can read and written data at high speeds. Therefore, this draws many interests in this area and is of practical utility for high density memory storage. The applications of the skyrmion drew many research interests after the recent findings on the interfacial DMI. Interfacial DMI is induced by Spin Orbit Coupling (SOC) between the exchange interaction between magnetic layers and heavy metal. This interfacial DMI gives the magnetic skyrmion stabilized topological structure, stabilizing it from annihilating at room temperature, hence making it feasible as a magnetic data memory device. In order to make use of this skyrmion as memory devices, it is crucial to understand its dynamics. However, there are limited studies in the non accelerating skyrmions dynamics. This project will introduce a new technique to quantify effective skyrmion mass in Synthetic Antiferromagnetic (SAF) layers. SAF was chosen because the interlayer coupling in SAF structure mitigate the occurrence of the skyrmion Hall effect. This avoids the skyrmion annihilation at the edge of the material. The aim of the thesis is to find the effective mass of magnetic skyrmions through extensive micromagnetic simulation driven by an alternating current in a SAF structure. The skyrmion dynamics is modelled using simple harmonic oscillator where the interlayer coupling force provides the restoring force in the system. These findings are further extended by observing the dependence of the effective mass on the materials parameter.